Diet of the Invasive Lionfish Pterois sp. in Broward County, Florida - Jasper, Sarah Ann; Thomas, J. D.; Kerstetter, David (NSUWorks, 2018)
The geographic range of invasive lionfish Pterois sp. currently extends throughout the Greater Caribbean in the western North Atlantic, prompting concerns about the impacts of its predation on local ecosystems. We focused on dietary habits of lionfish in Broward County, Florida, where there is only limited, anecdotal information on the species’ prey selection. Diet was determined using percent number, percent occurrence and percent weight, as well as the composite index of relative abundance (%IRI). A high percent teleost diet was documented during the third quarter (July-September) and a high crustacean diet in the fourth quarter (October-December), but seasonal effects by quarter or wet-dry analyses were insignificant. We observed an ontogenetic shift from a mainly crustacean diet to one consisting of mainly teleost fishes: the smallest lionfish size group (5-10 cm) had a 100% crustacean diet, whereas the largest size group (35-40 cm) had a 77% teleost and 23% crustacean diet. Our study results found no evidence that lionfish consumed commercially or recreationally targeted teleost species in these nearshore reef habitats.